Cognitive, affective and contextual predictors of subjective wellbeing - Galinha, Iolanda Costa (2011)
The article analyses the prediction of cognitive, affective and contextual factors to Subjective Wellbeing (SWB). Four different components of SWB were used in order to identify its different predictors. A sample of 303 adult students was collected and reassessed over a twomonth interval. Seven instruments were used to measure: Global Subjective Wellbeing; Satisfaction with Life in Domains; Positive and Negative State Affect; Positive and Negative Trait Affect; Standards of Comparison; Depression, Anxiety and Stress; Life Events; and SocioDemographic variables. Results indicated that Global SWB is predicted by Satisfaction with Life in Domains, and Positive and Negative State Affect. The cognitive dimension of SWB is predicted by Depression, Comparison Standards, State and Trait Affect, and several contextual variables. The affective dimension of SWB is predicted by Trait Affect, Depression, Anxiety, and the contextual variable of educational status. Results also indicated that intrapersonal variables are the main predictors of SWB, however contextual variables are also significant predictors. Each component of SWB (global, cognitive & affective) shows different predictors, stressing the importance of analysing and reporting separately the results of each component. Among the predictors of SWB over a two-month interval, state affective variables and contextual variables lose prediction power, while trait affective and cognitive variables gain prediction power.